FREQUENCY OF TWO ROOTS IN PERMANENT MANDIBULAR CANINE OF PAKISTANI POPULATION: A CONE BEAM COMPUTERIZED TOMOGRAPHY (CBCT) STUDY - Nauman Bari Khan; Muhammad Azhar; Nabeela Abbasi; Benish Mehmood (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Missed root/canal is one of the main causes of endodontic failure. Permanent mandibular canine is considered to be a single rooted tooth. The complex pattern of root canal system poses difficulty in the root canal treatment and the prognosis becomes uncertain if the debridement and obturation of the root canals is not satisfactory therefore our objective of the study is to assess frequency of two roots in permanent mandibular canine of Pakistani population using CBCT scan. METHODOLOGY: A descriptive; retrospective study was planned by using Cone Beam Computerized Tomography (CBCT) images of the past 02 year, i.e. December 2017 till November 2018. Images were assessed for the number of roots in permanent mandibular canines using software NNTVIEWER NewTOM. Data was entered and analyzed using SPSS 21. RESULTS: 134 permanent mandibular canines of 67 patients were studied. 64.2% of the images were of male patients while 35.8% were of females. Mean age of the patients was 48.12 ± 15.92 years. 7 (5.22%) out of 134 canines had two roots. 4 patients (5.97%) had canines with 2 roots of which 3 patients (4.48%) had bilateral two-rooted canines and 1 patient (1.49%) had unilateral two-rooted canines. Frequency of two roots in mandibular canines had no association with gender (p= 0.127). CONCLUSION: All mandibular permanent canines were single rooted but 5.2% of the permanent mandibular canines had two roots.